Antiquities laws and regulations issued in Jordan from 1923 to 2013 - Lash, Ahmed; Al-Syoof, Hala Qasem (Jordan Journal for History and Archaeology, 2022)
The Department of Antiquities, established in 1923, is one of the first governmental departments established after the foundation of the modern state of Jordan. For the purposes of organizing archaeological work, the Jordanian government has issued during the past hundred years several laws related to the legalization of archaeological work and the protection of antiquities, numbering seven, the first of which was the Law of Antiquities of 1925 and the last of which was Law No. 21 of 1988, followed by many amendments and regulations. The most recent of these was the Law Amending the Antiquities Law No. (55) of 2008. In this paper, we reviewed all antiquities laws, regulations, and amendments that occurred to them from 1923 to 2013, and discussed them, highlighting their strengths and weaknesses, and their contribution to protecting the Jordanian cultural heritage.